2005
DOI: 10.1093/jmt/42.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music Therapy on the Anxiety Levels and Sleep Patterns of Abused Women in Shelters

Abstract: The purpose of this study was to explore the effect of a music therapy procedure (music listening paired with progressive muscle relaxation) on the reduction of anxiety and improvement of sleep patterns in abused women in shelters. Twenty-eight women residing in 2 domestic violence shelters in a Midwestern city met with the researcher on 5 consecutive days for half-hour sessions. A pretest-posttest design with control and experimental groups was used. The dependent variables included: stait anxiety measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 0 publications
2
59
1
2
Order By: Relevance
“…In view of the results (P  0.0001 and F = 13.67), presenting the music affected on reducing the anxiety symptoms among the PTSD veterans and they comply with the results obtained from the Davis researches, Jeffler and Tat (2009), Ben Giotin, Pertet and Pekut (2009), Esvansdoviter and Sindal (2006) and Hernandez (2005. Findings of these studies emphasize on reducing the anxiety symptoms as a result of presenting the music to the patients.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In view of the results (P  0.0001 and F = 13.67), presenting the music affected on reducing the anxiety symptoms among the PTSD veterans and they comply with the results obtained from the Davis researches, Jeffler and Tat (2009), Ben Giotin, Pertet and Pekut (2009), Esvansdoviter and Sindal (2006) and Hernandez (2005. Findings of these studies emphasize on reducing the anxiety symptoms as a result of presenting the music to the patients.…”
Section: Discussionsupporting
confidence: 84%
“…Swansdoyter and Senidal (2006) found that music therapy is a reliable and effective way to treat the restlessness and anxiety among the patients. Hernandez (2005), in a research, examined the effect of music therapy on the level of anxiety and sleep patterns among the women abused. On the basis of findings, music therapy reduces the anxiety and improves the sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…Post-study consultations with participants showed that many had adopted relaxation training into their everyday lives. Relaxation training can be conducted at any time, regardless of location [29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Relaxation therapies have been proven to be effective against patient-specific insomnia symptoms in a number of studies 36) . In particular, music therapy has been reported to reduce anxiety and improve quality of sleep in several studies 37,38) . Relaxation techniques may be self-implemented at one's convenience and can result in improved sleep 39) .…”
Section: Discussionmentioning
confidence: 99%